1999
DOI: 10.1021/jp990014v
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Cations by Self-Assembled Monolayers of Crown Ethers

Abstract: Self-assembled monolayers (SAMs) of crown ether adsorbates on gold reversibly bind metal ions from aqueous solutions. The resulting changes of the electrochemical properties of the monolayers were monitored by impedance spectroscopy. The increased dielectric constant of the layer due to the complexation of ions results in an increase of the monolayer capacitance (C ML). Analysis of the response curves with a Langmuir isotherm enables the determination of association constants of the SAMs with various metal ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 17 publications
(34 reference statements)
2
98
0
Order By: Relevance
“…6 The molecular recognition process can be detected sensibly by IR spectroscopy, 3 quartz crystal microbalance (QCM), 4,5 surface plasmon resonance (SPR), 6 and electrochemical measurements. [7][8][9][10] The SAMs of ␣-helical peptides that oriented nearly vertically to the surface were successfully reported. 11 The molecular diameter of the helix is about 1 nm, which is more than 3-fold of that of general alkanethiols.…”
Section: Introductionmentioning
confidence: 99%
“…6 The molecular recognition process can be detected sensibly by IR spectroscopy, 3 quartz crystal microbalance (QCM), 4,5 surface plasmon resonance (SPR), 6 and electrochemical measurements. [7][8][9][10] The SAMs of ␣-helical peptides that oriented nearly vertically to the surface were successfully reported. 11 The molecular diameter of the helix is about 1 nm, which is more than 3-fold of that of general alkanethiols.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively recently, Reinhoudt et al (19)(20)(21)(22) and Bryce et al (23,24) reported, almost simultaneously, the incorporation of crownether groups into SAMs and their use as potential metal ion sensors. The Reinhoudt group used electrochemical impedance spectroscopy (EIS) for SAM characterization and to study the ion recognition processes (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…The Reinhoudt group used electrochemical impedance spectroscopy (EIS) for SAM characterization and to study the ion recognition processes (19)(20)(21)(22). This technique enables the detection of interfacial ion recognition phenomena when both guest ion and host monolayer are electrochemically inactive, by detecting changes of the charge-transfer resistance induced by metal ion binding (see Fig.…”
mentioning
confidence: 99%
“…[ 7 ] Moreover, OEG monolayers provide a very suited environment to coordinate cations by oxygen atoms. These binding motifs tend to form cage structures within the SAM, comparable to crown ethers [ 8,9 ] or cryptates. [ 10 ] Recently it was shown that OEG-based molecules with thiol anchors-which form striped patterns on gold nanoparticles in combination with short n -alkyl thiols-can effi ciently and selectively trap cations and thus serve as a sensitive sensor.…”
Section: Doi: 101002/adma201503911mentioning
confidence: 99%